1972
DOI: 10.4141/cjps72-125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Ethylene Evolution From Ethephon

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
(3 reference statements)
0
18
0
Order By: Relevance
“…3 and 4). Previous studies have also described the marked effect of temperature on ethylene evolution from ethephon applied to tomato fruit and sour cherry leaves (Flore and Bukovac, 1982;Lougheed and Franklin, 1972;Olien and Bukovac, 1978) and from pure ethephon solutions buffered to pH 6.0 (Olien and Bukovac, 1978). Warmer temperatures tended to cause taller plants and as growth temperatures increased, the effect of substrate-applied ethephon also tended to increase.…”
Section: Discussionmentioning
confidence: 93%
“…3 and 4). Previous studies have also described the marked effect of temperature on ethylene evolution from ethephon applied to tomato fruit and sour cherry leaves (Flore and Bukovac, 1982;Lougheed and Franklin, 1972;Olien and Bukovac, 1978) and from pure ethephon solutions buffered to pH 6.0 (Olien and Bukovac, 1978). Warmer temperatures tended to cause taller plants and as growth temperatures increased, the effect of substrate-applied ethephon also tended to increase.…”
Section: Discussionmentioning
confidence: 93%
“…Each bar represents a mean of six plants, and error bars represent SE. (Biddle et al, 1976;Klein et al, 1979;Lougheed and Franklin, 1972). Klein et al (1979) demonstrated that the half-life of ethephon decomposition decreases dramatically regardless of pH or vapor pressure as temperature increases from 20 to 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate efficacy is greater when applied at 35°C compared with applications at 24°C (McWhorter et al, 1980), whereas more slowly metabolized herbicides, such as mesotrione, have a greater efficacy when applied at lower temperatures (e.g., 25/15°C compared with 40/30°C day/night) (Godar et al, 2015). At high temperatures, the half-life of ethephon is less due to the rapid evolution from ethephon to ethylene (Biddle et al, 1976;Klein et al, 1979;Lougheed and Franklin, 1972). However, we have found no research conducted in a greenhouse environment to determine how average daily air temperature (ADT) during and following application (TEMP) affects the efficacy of ethephon on bedding plants.…”
mentioning
confidence: 99%
“…1912) and curing time is reduced (Chakroborty et al 1979;Domir and Foy 1976; Kwaih et al 1972;Hsieh et al 1912). Response varies considerably with degree of leaf ripeness (Domir and Foy 1976;Long et al 1974;Walker 1911), temperature at time of spray application (Lougheed and Franklin 1972) (Long et al 1974) or parts of leaves (Moon and Sin 1972) contacted by spray. The practical utility of ethephon would appear to be enhanced by using 100 mg per plant or less (Chakroborty etal.1979;Long et al1974;Weybrew et al 1973), by harvesting as soon as a color change becomes evident (Miles et al 1972), by curing with systems of good drying capacity (Weybrew et al 1913), and by treatment only of leaves at upper stalk positions (Walker 1977).…”
mentioning
confidence: 99%